Análise cristalográfica da solução sólida com estrutura tipo Tungstênio Bronze de niobato de potássio e estrôncio dopado com ferro - Lanfredi, Silvania [UNESP]; Nobre, Marcos Augusto Lima [UNESP]; Lima, Alan R. F. (Sociedade Brasileira de Química, 2010)
Solid solution of iron doped potassium strontium niobate with KSr2(FeNb4)O15-Δ stoichiometry was prepared by high efficiency ball milling method. Structural characterization was carried out by X-ray diffraction. Crystalline structure was analyzed by the Rietveld refinements using the FullProf software. The results showed a tetragonal system with the tetragonal tungsten bronze structure - TTB (a = 12.4631 (2) Å and c = 3.9322 (6) Å, V = 610.78 (2) Å³). In this work, the sites occupancy by the K+, Sr2+ and Fe3+ cations on the TTB structure were determined. NbO6 polihedra distortion and its correlation with the theoretical polarization are discussed.
Crystallographic analysis of the solid solution of iron doped potassium strontium niobate with tetragonal tungsten bronze structure
Keywords: KSr2(FeNb4)O15-δ solid solution; tetragonal tungsten bronze; Rietveld method